Differences between peptide profiles of extensive hydrolysates and their influence on functionality for the management of cow's milk allergy: A short review - Goh, Anne; Muhardi, Leilani; Ali, Adli; Liew, Woei Kang; Estrada-Reyes, Elizabeth; Zepeda-Ortega, Benjamin; Kudla, Urszula; van Neerven, R. J. Joost; Ulfman, Laurien H.; Lambers, Tim T.; Warner, John O. (Frontiers in Allergy, 2022)
Extensively hydrolyzed formulas (eHFs) are recommended for the dietary management of cow's milk protein allergy (CMPA) in non-exclusively breastfed infants. Studies show that peptide profiles differ between eHFs. This short review aims to highlight the variability in peptides and their ability to influence allergenicity and possibly the induction of tolerance by different eHFs. The differences between eHFs are determined by the source of the protein fraction (casein or whey), peptide size-distribution profile and residual β-lactoglobulin which is the most immunogenic and allergenic protein in bovine milk for human infants as it is not present in human breastmilk. These differences occur from the hydrolyzation process which result in variable IgE reactivity against cow's milk allergen epitopes by subjects with CMPA and differences in the Th1, Th2 and pro-inflammatory cytokine responses elicited. They also have different effects on gut barrier integrity. Results suggest that one particular eHF-casein had the least allergenic potential due to its low residual allergenic epitope content and demonstrated the greatest effect on restoring gut barrier integrity by its effects on mucin 5AC, occludin and Zona Occludens-1 in human enterocytes. It also increased the production of the tolerogenic cytokines Il-10 and IFN-γ. In addition, recent studies documented promising effects of optional functional ingredients such as pre-, pro- and synbiotics on the management of cow's milk allergy and induction of tolerance, in part via the induction of the production of short chain fatty acids. This review highlights differences in the residual allergenicity, peptide size distribution, presence of optional functional ingredients and overall functionality of several well-characterized eHFs which can impact the management of CMPA and the ability to induce immune tolerance to cow's milk protein.